The immediate effects of blood flow restriction training on upper limb muscle strength and fatigue level: a meta-analysis - Wang, Jian; Xu, Jie; Liu, Haiyang; Jiang, Lizhu (Frontiers in Physiology, 2025)
ObjectiveBlood flow restriction training (BFR training) has gained recognition as a potentially effective intervention; however, its specific effects on upper limb strength and fatigue levels remain inadequately explored. This study aims to systematically assess the impact of BFR training on immediate upper limb strength and fatigue through a meta-analytic approach, with the goal of providing empirical evidence to inform its practical implementation in clinical and athletic settings.MethodsSearch PubMed, CNKI, Web of Science and EBSCO databases, collect randomized controlled trials (RCTs) on the effects of BFR training on immediate upper limb strength and fatigue degree. Include and exclude literature through the Cochrane risk of bias tool. Employ Revman5.4 and Stata16.0 software for literature quality assessment and statistical analysis. Utilize sensitivity analysis and funnel plots to evaluate the stability of results and publication bias.ResultsA total of 32 articles and 524 subjects were incorporated. Meta-analysis revealed that upper limb BFR training significantly increased immediate muscle strength [SMD = 0.36, 95%CI (0.02, 0.70), P = 0.04]. Moreover, BFR training had a significant impact on fatigue degree [SMD = 1.38, 95%CI (0.81, 1.94), P < 0.00001]. Given the high heterogeneity of the two groups of studies (I2 = 77%, 88%), subgroup analysis demonstrated that BFR training could significantly enhance bench press strength [SMD = 0.40, 95%CI (0.07, 0.74), P = 0.02]. When the exercise intensity was 40%–70% of one repetition maximum (1RM) [SMD = 1.16, 95%CI (0.83, 1.50), P < 0.0001] and the compression intensity was ≥60% AOP [SMD = 0.64, 95%CI (0.24, 1.03), P = 0.0002], the effects on immediate upper limb strength reached the maximum and were statistically significant respectively. Subgroup analysis of fatigue degree indicated that BFR training could increase the blood lactate value [SMD = 2.15, 95%CI (1.06, 3.23), P < 0.0001] and subjective fatigue degree (rating of perceived exertion, RPE) [SMD = 1.11, 95%CI (0.36, 1.87), P = 0.004] of the subjects. Maximal effort [SMD = 2.61, 95%CI (2.14, 3.07), P < 0.0001] and compressive strength of ≥60% AOP [SMD = 2.64, 95%CI (1.35, 4.22), P = 0.001] had the greatest and significant effects on fatigue degree.ConclusionUpper limb BFR training can significantly enhance bench press strength. BFR training with 40%–70% 1RM and ≥60% AOP is more likely to promote immediate upper limb strength. Compared with resistance training without compression, exhaustive training may have a negative effect on upper limb muscle strength. BFR training combined with maximal effort and ≥60% AOP can increase the blood lactate value and subjective fatigue degree of the subjects.Systematic Review Registrationhttp://inplasy.com, identifier: INPLASY202430008.